2013
DOI: 10.7751/telopea2013004
|View full text |Cite
|
Sign up to set email alerts
|

A review of the genus <i>Stenochlaena</i> (Blechnaceae, subfamily Stenochlaenoideae)

Abstract: Stenochlaena is a small but widespread genus confined to the tropics and subtropics of the Old World. A key to the species, updated descriptions, distribution-maps, and detailed drawings are provided. Also included is a key to assist in separating several genera that are most often confused with Stenochlaena. There is morphological evidence suggesting that hybrids may exist between several species in Malesia. Although primarily a rainforest genus, the distribution patterns of the various species of Stenochlaen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…These include an Austrobuxus sp., a Brownlowia sp., a Calamus sp. that produces clavate pollen comparable to Calamuslobbiana (Harley, 1996), perhaps two species of (Morley, 1978(Morley, , 2000Chambers, 2013). We interpret the extinction of the mangrove Camptostemon from Sundaland to the disappearance of hypersaline mangroves following the development of wetter climates during the mid-Pleistocene, and the occurrence of Camptostemon at Perning in association with particularly dry conditions supports this proposition.…”
Section: Comparison Of Early Pleistocene and Presentday Javanese Flsupporting
confidence: 52%
See 1 more Smart Citation
“…These include an Austrobuxus sp., a Brownlowia sp., a Calamus sp. that produces clavate pollen comparable to Calamuslobbiana (Harley, 1996), perhaps two species of (Morley, 1978(Morley, , 2000Chambers, 2013). We interpret the extinction of the mangrove Camptostemon from Sundaland to the disappearance of hypersaline mangroves following the development of wetter climates during the mid-Pleistocene, and the occurrence of Camptostemon at Perning in association with particularly dry conditions supports this proposition.…”
Section: Comparison Of Early Pleistocene and Presentday Javanese Flsupporting
confidence: 52%
“…that produces clavate pollen comparable to Calamus lobbiana (Harley, ), perhaps two species of Camptostemon , Sonneratia ovalis , an extinct Sonneratia sp. producing pollen transitional with the extinct Florschuetzia semilobata , the podocarp Dacrydium , and a fern producing spores comparable to Stenochlaena milnei or Stenochlaena cummingii which are both currently restricted to Eastern Indonesia and the Philippines (Morley, , ; Chambers, ). We interpret the extinction of the mangrove Camptostemon from Sundaland to the disappearance of hypersaline mangroves following the development of wetter climates during the mid‐Pleistocene, and the occurrence of Camptostemon at Perning in association with particularly dry conditions supports this proposition.…”
Section: Palaeoecological and Palaeogeographical Interpretationmentioning
confidence: 99%
“…Furthermore, the fern is found growing on a wide range of tress and palms. 2 It is widely distributed throughout Malaysia, India, Myanmar, Yunnan in China, Laos, Thailand, Vietnam, Solomon Islands, south and northern Australia, islands of Fiji, Samoa and Tonga. 3 This species is also present in East Africa as well as on the Indian Ocean islands such as Madagascar.…”
Section: Introductionmentioning
confidence: 99%
“…Stenochlaena J. Smith belonging to the family Blechnaceae is a small genus consisting of only six species, and widely distributed in tropical and sub-tropical regions (Holttum, 1971;Chamber, 2013;Wang et al, 2013). Most of the species of the genus have both sterile and fertile pinnae.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the species of the genus have both sterile and fertile pinnae. Chamber (2013) reported that this genus is strongly dimorphic, in which fertile and sterile pinnae are located at the different fronds, with imparipinnate pinnae. Furthermore, Stenochlaena is charcterized by possessing radially symmetrical rhizome (Chamber, 2013); purplish-red to red fronds when young; sterile pinnae entire (Piggot, 1996); lanceolate to oblong-lanceolate, lateral veins arising from a closely parallel series of areolae; acrotischoid sori, that densely covering the dorsal surface or the lower surface of the fertile pinnae and not arrranged in discrete lines or dots; spores with a very thin and closely appressed perispore (Chamber, 2013).…”
Section: Introductionmentioning
confidence: 99%